Bible lands - Tubb, Jonathan N. (New York : A.A. Knopf : Distributed by Random House, 2000)
Photographs and text document life in Biblical times, surveying the clothing, food, and civilizations of a wide variety of cultures, including the Israelites, Babylonians, Persians, and Romans.
Includes index.
Keywords: Bible -- Antiquities -- Juvenile literature; Bible -- History of contemporary events -- Juvenile literature; Bible -- Antiquities; Middle East -- Antiquities -- Juvenile literature; Middle East -- Civilization -- To 622.